IMPROVING THE TEACHING OF RUNNING TECHNIQUES IN ATHLETICS - Karimov Bekzod Boyqobilovich; Axmatova Aziza (Journal Park Publishing, 2025)
The article describes the General characteristics of the process of improving the running technique, in particular, the running technique is analyzed on the example of middle-distance running. In conclusion, the main errors that occur due to an incorrect understanding of the nature of movements, inability to control your body, as well as affecting the effectiveness of the lesson are highlighted.
Keywords: Running technique, middle distance running, sports technique.